Pengembangan Pusat Edukasi Batik dan Penguatan Kelompok Sadar Wisata Desa Sumberpakem Kecamatan Sumberjambe Kabupaten Jember - Ima Masafatus Sholihah; Adilla Dhe Sal Sabilla; Aisa Aulia Nur Aini; Ladiya Husna Sariati; Diana Pretty Auliyassilmy; Neilil Amalia; Safina Wahyuningtiyas; Julitha Dwi Rosalinda; Eka Ardiansyah; Tasya Arista Kurnia Agustin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
The follow-up program from the Holistic Village Development and Empowerment Program (PHP2D), which has been well implemented, is the Village Development and Empowerment Program (P3D). The village's main target for this program is located in Sumberpakem, Sumberjambe District Jember Regency. Activities carried out in the village focus on one of the superior potentials that need to be developed, namely the batik craft known as Batik Sumberjambe. Development and empowerment were mainly carried out to develop batik education centres and strengthen tourism awareness groups. The reason for raising the topic is that the preservation of batik in Sumberpakem Village continues so that the wider community can know it. It can partner with the Tourism Office, Industry and Trade Office, Ministry of Tourism, and the organizers of the JFC (Jember Fashion Carnaval) international exhibition. This program development method was carried out offline by providing briefing and coaching to develop a batik education centre and strengthening tourism awareness groups to the community in Sumberpakem Village. The expected results from the program development are that the Sumberpakem Village community can produce good quality batik. Moreover, a batik Edu-tourism training centre is formed in power posts and cultural houses that can attract domestic and international tourists to visit Sumberpakem Village, Sumberjambe District Jember Regency.